Emerging roles of circular RNAs in cancer therapy-induced cardiotoxicity - Cheng, Ziji; Qin, Wanting; Li, Shaoling; Shao, Shuijin; Liu, Baonian (Frontiers in Cardiovascular Medicine, 2023)
Cancer therapy-induced cardiotoxicity (CTIC) is an important cause of death in cancer survivors which often results in the withdrawal or discontinuation of drugs. The underlying mechanisms of CTIC remain unclear. Circular RNAs (circRNAs) are a class of non-coding regulatory RNA molecules which have emerged in recent years. They are generated by back splicing and have powerful biological functions, including transcription and splicing, isolating or building macromolecular scaffolds to interfere with microRNA activity and signaling pathways, and acting as templates for translation. Moreover, circRNAs demonstrate high abundance and significant stability. CircRNAs can be used as novel biomarkers because they often function in a cell-type and tissue-specific manner. CircRNAs have attracted increasing attention in cardiovascular disease research, and recent studies exploring the role of circRNAs in CTIC have had promising results. This review will summarize the current understanding of circRNAs’ biogenesis, regulation and function. Their clinical potential as biomarkers, therapeutic agents and drug targets will also be explored.